Effects of oilseed rape green manure on phosphorus availability of red soil and rice yield in rice–green manure rotation system - Gu, Chi-ming; Li, Yin-shui; Yang, Lu; Dai, Jing; Hu, Wenshi; Yu, Chang-bing; Brooks, Margot; Liao, Xing; Qin, Lu (Frontiers in Plant Science, 2024)
Improving the nutrient content of red soils in southern China is a priority for efficient rice production there. To assess the effectiveness of oilseed rape as green manure for the improvement of soil phosphorus nutrient supply and rice yield in red soil areas, a long-term field plot experiment was conducted comparing two species of rape, Brassica napus (BN) and Brassica juncea (BJ). The effects of returning oilseed rape on soil phosphorus availability, phosphorus absorption, and yield of subsequent rice under rice–green manure rotation mode were analyzed, using data from the seasons of 2020 to 2021. The study found that compared with winter fallow treatment (WT) and no-tillage treatment (NT), the soil available phosphorus content of BN was increased, and that of BJ was significantly increased. The content of water-soluble inorganic phosphorus of BJ increased, and that of BN increased substantially. Compared with the WT, the soil organic matter content and soil total phosphorus content of BN significantly increased, as did the soil available potassium content of BJ, and the soil total phosphorus content of BJ was significantly increased compared with NT. The soil particulate phosphorus content of BJ and BN was significantly increased by 14.00% and 16.00%, respectively. Compared with the WT, the phosphorus activation coefficient of BJ was significantly increased by 11.41%. The rice plant tiller number under the green manure returning treatment was significantly increased by 43.16% compared with the winter fallow treatment. The green manure returning measures increased rice grain yield by promoting rice tiller numbers; BN increased rice grain yield by 9.91% and BJ by 11.68%. Based on these results, returning oilseed rape green manure could augment the phosphorus nutrients of red soil and promote phosphorus availability. Rice–oilseed rape green manure rotation could increase rice grain yield.